Health behaviors and the experience of vocal difficulties among students and teachers - Guzy, Anna (Logopedia Silesiana, 2022)
The article presents the results of research on health-related behaviors and the experience of subjective vocal ailments by students (n = 208) and teachers (n = 120). The procedure used the VHI (Voice Handicap Index) test to measure the level of voice disability and the IZZ test (Health Behavior Index) to measure the categories of health behaviors in the field of: correct eating habits, preventive behavior, positive mental attitude and health practices. Data from structured interview sheets were also used. In the case of teachers, there were statistically significant relationships between the results of the VHI test and correct eating habits, and between preventive behaviors. Among the studied students, a smaller number of statistically significant correlations between the occurrence of subjective vocal ailments and health habits was noted.